Оптимальное проектирование конструкций при комбинированном подходе к учету коррозии и защитных свойств антикоррозионных покрытий - Фридман, М.М. (Проблемы машиностроения, 2017)
Данное исследование посвящено созданию новой математической модели комбинированного подхода к учету коррозии и защитных свойств антикоррозионных покрытий. В качестве базового уравнения коррозии используется модель Долинского, которая позволяет учитывать влияние напряжений на коррозионный износ конструкций. Реализация данной модели продемонстрирована на примере оптимизации изгибаемых элементов прямоугольного сечения. Поэтапно получены аналитические решения по определению поперечных размеров и времени полной потери антикоррозионного покрытия данных элементов. В результате оптимизации найдены оптимальные начальные размеры сечения по критерию минимального объема конструкции. Предложенная модель, а также рассмотренный подход к ее реализации при оптимизации конструкций, работающих в условиях коррозии, могут быть использован как при аналитических решениях, так и с помощью численных методов. Запропоновано і реалізовано нову модель комбінованого підходу до обліку корозії і захисних властивостей антикорозійних покриттів на прикладі оптимізації згинальних елементів сталевих конструкцій. Як базове рівняння корозії використовується модель Долинського, що враховує вплив напруженого стану на кінетику корозії. Оптимізуються за критерієм мінімального обсягу початкові розміри згинального елемента прямокутного перерізу і знаходиться час повної втрати антикорозійного покриття конструкції. When constructing mathematical models of corrosion wear of structures, it is also necessary to take into account the work of protective coatings and determine the duration of the incubation period characterizing the durability of the protective coatings used. Protective coatings are barrier layers that impede the penetration of an aggressive medium to the surface of the structure and push back the onset of the process of intense corrosion. When calculating structures with protective coatings subjected to corrosive wear, it is necessary to take into account the joint operation of both the structural element itself and the protective coating, which leads to stresses in protective coatings, a more intensive decrease in the protective properties of these coatings and, as a result, premature failure. This study is devoted to the development of a new mathematical model of the combined approach to the calculation of corrosion and protective properties of anticorrosive coatings. As the basic equation of corrosion, the Dolinsky model is used, which allows one to take into account the effect of stresses on the corrosion wear of structures. The implementation of this model is demonstrated by the example of optimizing the bent elements of a rectangular section. Analytical solutions were obtained in stages to determine the transverse dimensions and time of complete loss of the anticorrosive coating of these elements. As a result of optimization, optimal initial section sizes were found by the criterion of the minimum volume of the structure. The proposed model, as well as the considered approach to its implementation when optimizing structures working under corrosion conditions, can be used both in analytical solutions and with the help of numerical methods.